(untitled) (World Science, 2022)
The article deals with the process of “waxing” of pipes and the choice of effective measures to prevent these negative phenomena. To assess the nature of asphalt-resin-paraffin deposits (ARPD) and select a further investigation scheme, the X-ray Spectral analysis was used. It is shown, that ARPD is a complex system structured by resinous-asphaltene substances and paraffin-naphthenic or paraffin-aromatic hydrocarbons. Mass transfer of solid deposits to the pipe wall is described by the Fick’s differential equation. In order to prevent "waxing" of pipes, compositions of antiadhesive fluorine glass-enamel coatings with a high class of surface cleanliness are proposed.